A civil-military headquarters for the EU: The Weimar Triangle initiative fuels the current debate - Claudia Major (Stiftung Wissenschaft und Politik (SWP), 2010)
In April 2010, the foreign ministers of the »Weimar Triangle« countries - Poland, France, and Germany - launched an initiative to strengthen the European Union's Common Security and Defence Policy (CSDP). The core objective of this initiative is to establish permanent civil-military planning and command structures for EU operations, in short: an EU Headquarters. This would be a significant improvement over the current state of affairs, in which the relevant structures are split between the EU and the member states' levels. This impedes the effective use of resources; it wastes time and reduces the operational efficiency of EU crisis management. Similar initiatives have failed in the past due to political concerns. If the EU wants to remain engaged in crisis management and carry out the complex civil-military tasks, it cannot do without appropriate internal EU structures
Keywords: 350